Psychosocial Factors Associated with Youth Political Participation: A Systematic Review: Factores psicosociales asociados a la participación política juvenil: Una revisión sistemática - Mendoza-Rincón, Beatriz-Milagros; Riano-Garzon, Manuel; Cepeda-Pineda, Daniel; Araque-Castellanos, Franlet; González- Gutiérrez, Orlando; Rivera-Porras, Diego (Gaceta Médica de Caracas, 2025)
Objective: This article presents a systematic review aimed at identifying and analyzing the effects of various sociodemographic, psychological, and contextual variables on the political participation of young people. Method: The review of studies was conducted using the PRISMA method and the AMCPLT strategy. Thirty-five quantitative and qualitative research studies, published between 2009 and 2024, were selected from the PubMed, Scopus, and Web of Science databases. These studies were conducted in Europe, Latin America, Asia, Africa, and Oceania, involving young people aged 15 to 29 years.